Lignocellulosic Bioethanol Efficiency of Different Sweet Sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr.) Genotypes in Şanlıurfa Ecological Conditions - Efendioğlu Çelik, Ayşegül; Aksoy, Mine; Dok, Mahmut; Aydın, Kadir; Yucel, Celal (My University, 2023)
The use of products with high biomass yield per unit area as a renewable energy source, which are not consumed primarily for food purposes or can be used for multi-purposes, is of great importance in terms of food safety. For this purpose, sweet sorghum plant, which can grow in salty-alkaline soils, tolerant to drought and short-term floods, and has wide adaptability, has gained importance as a lignocellulosic bioethanol raw material in recent years. The aim of this study is to theoretically determine the lignocellulosic bioethanol yield of 21 different sweet sorghum (Sorghum bicolor var. saccharatum (L.) Mohlenbr.) genotypes grown under second crop conditions in the ecology of Şanlıurfa province, obtained from domestic and foreign sources. In the study, sweet sorghum pulp from plant sap was used as lignocellulosic bioethanol raw material. The cellulose and hemicellulose contents of the pulp were determined and the amount of lignocellulosic bioethanol that could be obtained per decare was calculated by using the bioethanol conversion rates. According to the data obtained, the highest yield was obtained from UNL-Hybrid-3 (805.5 L/da), Theis (766.5 L/da), Smith (698.1 L/da) genotypes. In order to solve problems such as increasing the octane of gasoline, reducing greenhouse gas emissions and gasoline imports, it is recommended that these three genotypes be cultivated and disseminated for lignocellulosic bioethanol production in Şanlıurfa ecological conditions.
Keywords: Renewable energy; Sweet sorghum; Pulp; Cellulose